Electrostatic Spinning based on Aqueous Polyurethane Block‐Modified Polycaprolactone and Its Hydrophilicity Study. Issue 12 (28th October 2021) - Wang, Faqiang; Wang, Xueting; Xi, Yanni; Liu, Kexin; Li, Zhanxiong
Abstract: In this study, waterborne polyurethane hydrophilic block copolymer PCL‐ b ‐WPU is obtained through step‐growth addition polymerization reaction to improve the hydrophilicity of polycaprolactone (PCL). Then, films are prepared via solution casting method and electrospinning. PCL‐ b ‐WPU nanofibrous membranes have a higher initial water contact angle of 106°, but they can be completely wetted from the surface to the back within 120 s, with good wet absorption and quick‐drying performance. Hollow fibers are fabricated via coaxial electrospinning by controlling the process parameters. PCL‐ b ‐WPU is used as shell material and polyoxyethylene as the core. Low‐field nuclear magnetic resonance technology is used to analyze the moisture distribution and the state of water within solid, porous, and porous hollow fibers. Their bound water is 14.5%, 27.5%, and 31.1%, respectively. These results suggest that the introduction of the WPU chain and the construction of a rough surface significantly improve the hydrophilicity of PCL. PCL‐ b ‐WPU membranes are expected to be further developed and utilized for moisture‐absorbing and quick‐drying textiles, wound dressings, and biological scaffolds. Abstract : The hydrophilic polycaprolactone (PCL‐ b ‐WPU) is successfully synthesized through addition polymerization modification. After testing, it can be confirmed that the PCL‐ b ‐WPU membrane made by electrospinning has good wet absorption and quick drying performance. The bound water content of porous hollow fibers is up to 31.1%.